1982
DOI: 10.1203/00006450-198204000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Taurocholate by Hepatocytes Isolated from Developing Rats

Abstract: Summaryon Purina rat chow and water ad libitum. Male rats were utilizedTo further define developmental changes in bile acid metabolism, we determined the kinetics of taurocholate uptake by hepatocytes isolated from Sprague-Dawley rats at 7, 14,21,28, and 56 days of age. There was a progressive increase in taurocholate uptake with age. The uptake process exhibited saturable kinetics in every age group with a maximum uptake velocity attained above a taurocholate concentration of 200 pM. There were no differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…The net effect is that taurocholate will not accumulate within the hepatocyte above the capacity of binding proteins native to suckling rat liver in the absence of a large, inwardly directed concentration gradient. This could explain our observation that suckling rat hepatocytes were able to attain a bile acid concentration similar to mature cells du~ing preloading despite a lower initial uptake velocity as documented earlier (5). Earlier and greater "unloading" seemed to occur once this large inward gradient was removed.…”
Section: Resultssupporting
confidence: 61%
“…The net effect is that taurocholate will not accumulate within the hepatocyte above the capacity of binding proteins native to suckling rat liver in the absence of a large, inwardly directed concentration gradient. This could explain our observation that suckling rat hepatocytes were able to attain a bile acid concentration similar to mature cells du~ing preloading despite a lower initial uptake velocity as documented earlier (5). Earlier and greater "unloading" seemed to occur once this large inward gradient was removed.…”
Section: Resultssupporting
confidence: 61%
“…During fetal and neonatal life, synthesis of BA has been postulated to occur via an alternate pathway, which has lithocholic acid and 3 8-hydroxy-5 cholenoic acid as intermediates (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). There appears to be synthesis via the usually accepted pathway as well, however, the alternate pathway seems to be of major importance in fetal life (1 3).…”
Section: Discussionmentioning
confidence: 99%
“…This state of hypercholanemia, reflecting an immaturity of the enterohepatic circulation, has since been corroborated by other investigators using similar radioimmunoassays (4, 25, 27), and "physiologic cholestasis" is now recognized as a normal developmental condition. The factors responsible for physiologic cholestasis have not yet been completely defined in the human infant; data obtained in animal models have documented the immaturity of several of the processes involved in the enterohepatic circulation of BA (hepatic uptake, conjugation, excretion, and intestinal absorption) (5, 10,23,24,26). However, the presence of marked species differences, as has been well demonstrated for other fetal hepatic excretory mechanisms, makes it difficult to extrapolate these data to the human infant.…”
mentioning
confidence: 99%
“…Recent studies utilizing hepatocytes and basolateral liver plasma membrane vesicles prepared from developing rats have shown that bile acid uptake is markedly decreased probably as a result of fewer functional bile acid carriers on the sinusoidal membrane of the hepatocyte (9,10). These findings led us to the hypothesis that the low transport capacity of the developing liver for bile acids might well result in an acinar distribution for bile acid uptake which differed from the adult.…”
mentioning
confidence: 85%